Assessment of Intraoperative Intra-articular Morphine and Clonidine Injection in the Acute Postoperative Period After Hip Arthroscopy - Cogan, Charles J. (Orthop J Sports Med, 2016)
BACKGROUND: Previous authors have suggested that intra-articular morphine and clonidine injections after knee arthroscopy have demonstrated equivocal analgesic effect in comparison with bupivacaine while circumventing the issue of chondrotoxicity. There have been no studies evaluating the effect of intra-articular morphine after hip arthroscopy. PURPOSE: To evaluate the efficacy of intra-articular morphine in combination with clonidine on postoperative pain and narcotic consumption after hip arthroscopy surgery for femoroacetabular impingement. STUDY DESIGN: Cohort study; Level of evidence, 3. METHODS: A retrospective chart review was performed on 43 patients that underwent hip arthroscopy for femoroacetabular impingement at a single institution between September 2014 and May 2015. All patients received preoperative celecoxib and acetaminophen, and 22 patients received an additional intra-articular injection of 10 mg morphine and 100 μg of clonidine at the conclusion of the procedure. Narcotic consumption, duration of anesthesia recovery, and perioperative pain scores were compared between the 2 groups. RESULTS: Patients who received intra-articular morphine and clonidine used significantly less opioid analgesic (mEq) in the postanesthesia recovery (median difference, 17 mEq [95% CI, –32 to –2 mEq]; P = .02) compared with the control group. There were no differences in time spent in recovery before hospital discharge or in visual analog pain scores recorded immediately postoperatively and at 1 hour after surgery. CONCLUSION: Intraoperative intra-articular injection of morphine and clonidine significantly reduced the narcotic requirement during the postsurgical recovery period after hip arthroscopy. The reduction in postsurgical opioids may decrease adverse effects, improve overall pain management, and lead to better quality of recovery and improved patient satisfaction.